2013
DOI: 10.1103/physrevc.88.068201
|View full text |Cite
|
Sign up to set email alerts
|

Shear viscosity due to Landau damping from the quark-pion interaction

Abstract: We have calculated the shear viscosity coefficient η of the strongly interacting matter in the relaxation time approximation, where a quasiparticle description of quarks with their dynamical masses is considered from the Nambu-Jona-Lasinio model. Due to the thermodynamic scattering of quarks with pseudoscalar-type condensate (i.e., pion), a nonzero Landau damping will be acquired by the propagating quarks. This Landau damping may be obtained from the Landau cut contribution of the in-medium self-energy of a qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 48 publications
(33 reference statements)
0
43
0
Order By: Relevance
“…The understanding of the elliptic flow observed at heavy-ion collider experiments in terms of dissipative hydrodynamics, in particular the description of the elliptic flow by a low shear viscosity-to-entropy density ratio of the deconfined quark phase stimulated extensive studies of the shear viscosity of strongly interacting matter. Transport coefficients of QCD matter have been investigated using various methods including perturbative QCD [23][24][25][26][27][28][29][30], equilibrium correlation functions within the Kubo formalism [31][32][33][34][35][36][37][38], transport simulations of the Boltzmann equation [39][40][41][42], relaxation-time approxima-arXiv:1702.04291v3 [nucl-th] 11 Jun 2017 tion to the Boltzmann equation [43][44][45][46], lattice methods [47][48][49][50][51][52] and holographic methods [53][54][55][56][57][58] with the main emphasis on the low values of the shear viscosityto-entropy density ratio indicated by the hydrodynamical modeling of heavy-ion collision experiments [1][2][3][4][5]…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of the elliptic flow observed at heavy-ion collider experiments in terms of dissipative hydrodynamics, in particular the description of the elliptic flow by a low shear viscosity-to-entropy density ratio of the deconfined quark phase stimulated extensive studies of the shear viscosity of strongly interacting matter. Transport coefficients of QCD matter have been investigated using various methods including perturbative QCD [23][24][25][26][27][28][29][30], equilibrium correlation functions within the Kubo formalism [31][32][33][34][35][36][37][38], transport simulations of the Boltzmann equation [39][40][41][42], relaxation-time approxima-arXiv:1702.04291v3 [nucl-th] 11 Jun 2017 tion to the Boltzmann equation [43][44][45][46], lattice methods [47][48][49][50][51][52] and holographic methods [53][54][55][56][57][58] with the main emphasis on the low values of the shear viscosityto-entropy density ratio indicated by the hydrodynamical modeling of heavy-ion collision experiments [1][2][3][4][5]…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the one-loop results are restricted to T 210 MeV. We compare our results to those from a kinetic approach using the two-favor NJL model [14] (open circles) and [51] (open triangles). Our values based on the Kubo formalism are larger but feature the same order of magnitude and the same qualitative behavior.…”
Section: Spectral Width At One-loop Levelmentioning
confidence: 99%
“…8. The term involving the Bose distribution describes Landau damping, a process also known from high-T QCD calculations [50], and recently applied to the calculation of the shear viscosity from kinetic theory [51]. In the NJL model Landau damping arises from the scattering of quarks on the mesonic collective modes in the thermal medium.…”
Section: Spectral Width At One-loop Levelmentioning
confidence: 99%
“…Interestingly the NJL model has also been studied within the Monte Carlo framework [101,102]. Studies of various transport coefficients in the NJL model framework have also been reported recently [103,104].…”
Section: Introductionmentioning
confidence: 99%